The prognostic value of ferritinemia level in patients with chronic hepatitis C - N. C. Sargsyants; E. H. Grigoryan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study the effect of various factors on the blood ferritin level in patients with chronic hepatitis C (CHC) and baseline ferritin level on treatment response rate of pegilated interferon α-2a (PEG-IFN α-2a) combined to ribavirin (RBV). Material and methods. The level of ferritin was determined in 67 patients with CHC by two solid-phase sandwich immunoenzymatic assays. In 32 patients, who received PEG-IFN α-2a and RBV, it was determined on starting point, on the 12th week and after termination of therapy. Logistical regression has been applied to study effect of ferritin and other variables on frequency of sustained virologic response (SVR). Results. Elevated ferritin level was revealed in 34,3% of patients, and it was significantly higher in men, than in women (326,0±38,4 vs 108,2±44,7 ng/dl, p <0,05). The average level of ferritin in the patients included in PEGIFN α-2a and RBV group, prior to onset of treatment was normal (241,4±33,1), on the 12th week of treatment it turn to be elevated in 90% of patients with average level of 703,5±133,4 ng/dl (p=0,009 at comparison to initial level), and after the end of treatment course elevation was observed in 66,6% of patients at average value of 473,6±96,3 ng/dl (p=0,044 at to starting point, p=0,07 at comparison to the 12-th week data). By comparison of average levels of ferritin in patients with SVR at intake of PEG-IFN α-2a in combination to RBV and in patients without SVR the difference was also apparent, especially at the 12th week.Conclusions. Application of logistical regression analysis demonstrated, that the baseline ferritin level is independent predictor of sustained virologic response at treatment by pegilated interferon α-2a with ribavirin.